SURGICO-THERAPEUTIC MANAGEMENT OF OCULAR SQUAMOUS CELL CARCINOMA IN A BULLOCK: A CASE REPORT - Chandrashekhar, T; Shruti, JS; Amith, NG; Kshama, MA; Pramodh, JK (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Squamous cell carcinoma of eyeis one of the most common type of skin cancer reported in cattle. It is a very painful fatal disorder which manifests initially as a small nodular growth in the adnexa of eye. Furthur, it represents one of the most economically important neoplasm in large animals and its economic impact is mainly due to carcass condemnation, production losses as well as expenditure of treatment and management. The average age of occurrence of SCC in cattle is 8 years (Cordy, 1990) and the tumours are said to be uncommon in cattle less than 5 years and rare and hardly seen in cattle less than 3 years of age (Rhadostits et al. 2000). Cattle with unpigmented skin around the eye have been reported to be more susceptible to cancer eye.